The Effects of Individual vs Team Sports on Perceived Stress, Sports Anxiety and Sports Motivation among Competitive Youth Athletes - Teh, R.; Rajkumar Krishnan, Vasanthi (DAA Scientific Section (Spain), 2022)
Objective: The objective of the study was to determine if there is a significant difference between perceived stress, sports anxiety and sports motivation among competitive young athletes in individual and team sports.